Does Laboratory Matters in Today’s High School Learning Environment? - Khairil Asnan Haedar; Muhammad Ainurridho; Suci Indah Cahyani (Har Press Indonesia, 2024)
The study focused into the relationship between laboratory importance perceptions and academic performance in biology among private and public school students. Study sample involving 165 students from 5 private and 6 public senior high school across South Sulawesi, Indonesia. All private school only possessed an integrated science lab, while all public school owned at least 3 science labs (biology, chemistry, and physics). Evaluation on laboratory importance and biology test results proceed to reveal the importance of having designed laboratory to enhance biology learning outcome in the middle of technological advancement, where learning resource vary across platforms. Surprisingly, private schools, despite having lower scores in laboratory importance perception, achieved superior results in biology tests compared to public schools. This suggests that while laboratory experiences are valuable, they may not be the sole determinants of academic success. Other factors like teaching methods, curriculum depth, and student motivation likely contribute significantly. These findings highlight the complexity of factors influencing student performance in biology and the need for a comprehensive approach to education. Understanding these dynamics can inform educational policies including funds allocation in a school and practices to optimize learning outcomes in biology subjects.